Investigation of the influence of groundwater flow on horizontal ground heat exchangers using numerical simulations - Rammler, Mario; Suft, Oliver; Bertermann, David (Hydrological Research Letters, 2025)
In contrast to unsaturated soil conditions, advective heat transport dominates in aquifers. Consequently, groundwater flow can affect the efficiency of geothermal horizontal ground heat exchangers (HGHEs) and the development of downstream thermal plumes. In contrast to deeper geothermal systems, this has not been investigated in detail for HGHEs due to their shallow installation depths. In order to address this issue, in this study, the effects of different groundwater flow conditions on a theoretical unidirectional HGHE were evaluated using the FEFLOW® finite element simulation system. A total of 81 variants with different groundwater levels, flow velocities and flow directions were considered in the numerical simulations. The results showed a significant increase in HGHE efficiency with increasing groundwater level (GWL) and flow velocity. In addition, significantly higher heat gains were obtained when the groundwater flow direction was orthogonal to the HGHE. The lateral spread of the thermal plumes was greatest for orthogonal flow directions, high flow velocities and groundwater levels slightly above the HGHE. The presented FEFLOW® approach was suitable to investigate the effects of different hydraulic subsurface conditions on a unidirectional HGHE and should be vali-dated with real measured data in further research.
CRIS-Team Scopus Importer:2025-03-28
Keywords: advective heat transport; FEFLOW®; groundwater; horizontal ground heat exchangers; numerical simulations